Polarizing film and method for manufacturing the same

By using PVA, monoorganoboric acid and diorganoboric acid in the manufacturing process of the polarizing film, and controlling the mass ratio and content of boron elements, the problems of large shrinkage force and poor moisture and heat resistance in the prior art are solved. It achieves low shrinkage force and high humidity resistance, and is suitable for LCD panels and OLED panel applications.

CN114008497BActive Publication Date: 2025-02-25KURARAY CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202080046465.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-06-27
Filing Date
2020-06-25
Publication Date
2025-02-25
Estimated Expiration
2040-06-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide a polarizing film with low shrinkage force, excellent optical performance and high humidity resistance at high temperatures. Especially when used in LCD panels and OLED panels, the warping and fading of the polarizing films have not been completely solved.

Method used

By using a polarizing film containing PVA, monoorganoboric acid and diorganoboric acid, the mass ratio and content of the boron element are controlled to achieve low shrinkage force and high humidity resistance of the polarizing film. The specific method includes performing multiple impregnation treatments on the PVA film in an aqueous solution of boron-containing compound during the manufacturing process to ensure uniform adsorption and cross-linking of boron elements.

Benefits of technology

The low shrinkage force and high humidity resistance of the polarizing film at high temperatures are achieved, and the warping and fading problems of LCD panels and OLED panels are avoided, and the stability and performance of the equipment are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114008497B_ABST
    Figure CN114008497B_ABST
Patent Text Reader

Abstract

A polarizing film, comprising: polyvinyl alcohol (A), at least one boron-containing compound (B) selected from a monoorganic boronic acid represented by the following formula (I) and a compound that can be converted into the monoorganic boronic acid in the presence of water, and at least one boron-containing compound (C) selected from a diorganic boronic acid represented by the following formula (II) and a compound that can be converted into the diorganic boronic acid in the presence of water, wherein the mass ratio (B / C) of the boron element derived from the boron-containing compound (B) to the boron element derived from the boron-containing compound (C) is 4.0 to 8.0, and the content of the boron element derived from the boron-containing compound (C) is 0.05 to 0.3 parts by mass relative to 100 parts by mass of polyvinyl alcohol (A). The polarizing film has low shrinkage force at high temperatures and excellent moisture and heat resistance. [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 Connected to the organic boronic acid group via a boron-carbon bond]. [In formula (II), R 2 is a divalent aliphatic group having 1 to 20 carbon atoms, R 2 Connected to the organic boronic acid group through a boron-carbon bond]. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polarizing film having a small shrinkage force at high temperature and excellent optical properties and moisture and heat resistance, and a method for producing the same. Background Art

[0002] Polarizing plates that transmit and shield light are the basic components of liquid crystal displays (LCDs) along with liquid crystals that change the polarization state of light. In addition, in recent years, circular polarizing plates combined with 45° phase plates have been used to prevent external light reflection in organic electroluminescent displays (OLEDs). In order to prevent the fading of the polarizing film or the shrinkage of the polarizing film, many polarizing plates and circular polarizing plates have a structure in which a protective film such as a triacetyl cellulose (TAC) film is attached to the surface of the polarizing film. As a polarizing film, the mainstream is to adsorb iodine-based pigments (I2O2) on a matrix obtained by uniaxially stretching a polyvinyl alcohol film (hereinafter sometimes referred to as "PVA") 3 - ,I 5 - A polarizing film obtained by using dichroic pigments such as dichroic dyes, etc.

[0003] LCD is used in a wide range of small devices such as calculators and watches, smart phones, laptops, liquid crystal displays, liquid crystal color projectors, liquid crystal televisions, car navigation systems, indoor and outdoor measuring equipment, etc., and OLED is used in a wide range of smart phones, OLED TVs, smart watches, etc. These devices require thinness and flexibility, and with this, the thinning of LCD panels and OLED panels has been promoted in recent years. As a result, the occurrence of warping of LCD panels and OLED panels, and the fading of polarizing plates and circular polarizing plates under high temperature and high humidity have become problems. The main reason for the warping of LCD panels and OLED panels is said to be that the polarizing film shrinks at high temperatures, requiring a polarizing film with a small shrinkage force at high temperatures. In addition, the main reason for the fading of polarizing plates and circular polarizing plates under high temperature and high humidity is the decomposition of iodine complexes caused by moisture in iodine-based polarizing films. In the past, it was dealt with by reducing the moisture permeability of the protective film, but with the thin filmization of the protective film, the moisture permeability of the protective film becomes higher, and therefore, it is also required that the stability of the iodine complex under high temperature and high humidity is also high. Polarizing film, that is, the so-called iodine-based polarizing film with excellent moisture and heat resistance.

[0004] However, as means for reducing the shrinkage force of the polarizing film, there are known methods of reducing the amount of boric acid in the PVA film and providing a step of drying the PVA film between the boric acid treatment step and the water washing step (Patent Document 1), controlling the ratio of film thickness and stretching ratio while thinning the polarizing film (Patent Document 2), and appropriately controlling the drying temperature according to the moisture content of the PVA film (Patent Document 3).

[0005] However, when the amount of boric acid in the polarizing film is reduced as described in Patent Document 1, it is difficult to sufficiently reduce the shrinkage force while having high resistance to moisture and heat.

[0006] When the polarizing film is thinned as described in Patent Document 2, there is a problem that the moisture-heat resistance of the polarizing film itself is reduced.

[0007] A polarizing film with low shrinkage force can be manufactured by appropriately managing the drying temperature according to the moisture content of the PVA film as described in Patent Document 3. However, in the method described in Patent Document 3, a film with a high moisture content is dried at a high temperature, and thus, the optical properties may be reduced, the polarizing film may be dissolved and broken during drying, and it is difficult to implement industrially.

[0008] Next, as means for improving the moisture and heat resistance of iodine-based polarizing films, there are known means of cross-linking a PVA film with a polyaldehyde (Patent Document 4), a method of manufacturing a polarizing film by stretching a PVA film in an aqueous solution containing a diorganoboric acid compound (Patent Document 5), a method of treating a PVA film with an organic boric acid compound (Patent Document 6), a method of treating a PVA film with a diorganoboric acid (Patent Document 7), a method of obtaining a polarizing film using PVA with high isotacticity (Patent Document 8), a method of obtaining a polarizing film using PVA with a high degree of polymerization (Patent Document 9), etc.

[0009] However, in the method using a polyvalent aldehyde described in Patent Document 4, since the aldehyde easily volatilizes and the concentration control is difficult, it is difficult to implement it industrially.

[0010] In the method of manufacturing a polarizing film by stretching a PVA film in an aqueous solution containing a diorganoboric acid compound and the method of treating a PVA film with an organic boric acid compound described in Patent Documents 5 and 6, although a polarizing film with excellent moisture and heat resistance can be obtained, a large number of breaks occur during stretching, making it difficult to implement industrially or the reduction of the shrinkage force is insufficient.

[0011] The method of treating with a diorganoboric acid described in Patent Document 7 can obtain a polarizing film having excellent resistance to moisture and heat, but since diorganoboric acid is unstable to water and decomposes, it is difficult to control the concentration and thus difficult to implement industrially.

[0012] If PVA having high syndiotacticity is used as described in Patent Document 8, a polarizing film having high resistance to moist heat can be obtained. However, this PVA has high crystallinity and needs to be stretched at high temperature, which makes it difficult to implement industrially.

[0013] When PVA with a high degree of polymerization is used as described in Patent Document 9, a polarizing film having high resistance to moisture and heat can be obtained. However, the shrinkage force becomes high, and therefore it is difficult to achieve both low shrinkage force and high resistance to moisture and heat.

[0014] Prior art literature

[0015] Patent Literature

[0016] Patent Document 1: Japanese Patent Application Publication No. 2013-148806

[0017] Patent Document 2: Japanese Patent Application Laid-Open No. 2001-343522

[0018] Patent Document 3: Japanese Patent Application Laid-Open No. 2018-004707

[0019] Patent Document 4: Japanese Patent Application Laid-Open No. 6-235815

[0020] Patent Document 5: KR10-2014-0075154

[0021] Patent Document 6: International Publication No. WO2018 / 021274

[0022] Patent Document 7: Japanese Patent Application Publication No. 2018-180022

[0023] Patent Document 8: Japanese Patent Application Laid-Open No. 6-265727

[0024] Patent document 9: Japanese Patent Application Laid-Open No. 01-084203. Summary of the invention

[0025] Problems to be solved by the invention

[0026] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a polarizing film having a small shrinkage force at high temperature and excellent resistance to moisture and heat.

[0027] Means for solving problems

[0028] The above-mentioned problem is solved by providing the following polarizing film, which comprises: PVA (A), at least one boron-containing compound (B) selected from the monoorganic boronic acid represented by the following formula (I) and a compound that can be converted into the monoorganic boronic acid in the presence of water, and at least one boron-containing compound (C) selected from the diorganic boronic acid represented by the following formula (II) and a compound that can be converted into the diorganic boronic acid in the presence of water, wherein the mass ratio (B / C) of the boron element derived from the boron-containing compound (B) to the boron element derived from the boron-containing compound (C) is 4.0 to 8.0, and the content of the boron element derived from the boron-containing compound (C) is 0.05 to 0.3 parts by mass relative to 100 parts by mass of polyvinyl alcohol (A).

[0029] [Chemistry 1]

[0030]

[0031] [In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 Connected to the organic boronic acid group via a boron-carbon bond]

[0032] [Chemistry 2]

[0033]

[0034] [In formula (II), R 2 is a divalent aliphatic group having 1 to 20 carbon atoms, R 2 Connected to the organic boronic acid group via a boron-carbon bond]

[0035] At this time, R 1 and R 2 It is preferably a saturated aliphatic group. 1 and R 2 It is also preferably an aliphatic hydrocarbon group. 1 The number of carbon atoms in R is preferably 2 to 5. 2 More preferably, it is 3 to 5.

[0036] The above-mentioned problem is also solved by providing a method for manufacturing the aforementioned polarizing film, in which the method for manufacturing the polarizing film comprises a dyeing treatment of dyeing the PVA film with a dichroic pigment and a stretching treatment of uniaxially stretching the film, comprising: a treatment of immersing the film in an aqueous solution containing a boron-containing compound (B) and a treatment of immersing the film in an aqueous solution containing a boron-containing compound (C).

[0037] At this time, it is preferred that: after the aforementioned PVA film is immersed in an aqueous solution containing a boron-containing compound (B), it is immersed in an aqueous solution containing a boron-containing compound (C). Further, it is more preferred that: the content of boron element derived from the boron-containing compound (B) in the aforementioned PVA film after the immersion in the aqueous solution containing the boron-containing compound (B) is 1.3 parts by mass or less relative to 100 parts by mass of PVA (A).

[0038] Effects of the Invention

[0039] The polarizing film of the present invention has a small shrinkage force at high temperature and excellent moisture and heat resistance. Therefore, by using the polarizing film of the present invention, an LCD panel or OLED panel that is difficult to warp at high temperature and has excellent moisture and heat resistance can be obtained. In addition, according to the manufacturing method of the present invention, such a polarizing film can be manufactured. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 is the polarizing film obtained in Example 1 1 H-NMR spectrum.

[0041] Figure 2This is a graph in which the shrinkage force is plotted on the horizontal axis and the attenuation coefficient of the PVA-iodine complex is plotted on the vertical axis for the polarizing films of Examples 1 and 2 and Comparative Examples 1 to 12. DETAILED DESCRIPTION

[0042] The polarizing film of the present invention comprises: PVA (A), at least one boron-containing compound (B) selected from a monoorganic boronic acid represented by the following formula (I) and a compound that can be converted into the monoorganic boronic acid in the presence of water, and at least one boron-containing compound (C) selected from a diorganic boronic acid represented by the following formula (II) and a compound that can be converted into the diorganic boronic acid in the presence of water, wherein the mass ratio (B / C) of the boron element derived from the boron-containing compound (B) to the boron element derived from the boron-containing compound (C) is 4.0 to 8.0, and the content of the boron element derived from the boron-containing compound (C) is 0.05 to 0.3 parts by mass relative to 100 parts by mass of PVA (A).

[0043] The polarizing film of the present invention has a small shrinkage force and excellent moisture and heat resistance. It is believed that such an effect is achieved by attaching the boron-containing compound (B) required for reducing the shrinkage force to the PVA film and cross-linking the PVA (A) with the boron-containing compound (B) and the boron-containing compound (C) in an appropriate ratio.

[0044] [Chemistry 3]

[0045]

[0046] Monoorganoboric acid is a compound represented by the above formula (I), which has one organic boronic acid group [-B(OH) 2 R of formula (I) 1 is a monovalent aliphatic group having 1 to 20 carbon atoms. The organic boronic acid group has a structure in which a boron atom to which two hydroxyl groups are bonded is bonded to a carbon atom. In the compound represented by formula (I), R 1 Connected to the organic boronic acid group through a boron-carbon bond. 3 ], the boron atom is bonded to three hydroxyl groups, whereas the difference of the organic boronic acid group is that it has a boron-carbon bond. In addition, the boron-carbon bond of the organic boronic acid group will not be hydrolyzed, and therefore, it is stable even in the presence of water. As a boron-containing group that can be converted into an organic boronic acid group in the presence of water, the organic boronic acid ester group described later can be cited as a representative, but is not limited thereto.

[0047] [Chemistry 4]

[0048]

[0049] The diorganoboric acid is a compound represented by the above formula (II) and has two organic boronic acid groups [-B(OH) 2In formula (II), R 2 is a divalent aliphatic group having 1 to 20 carbon atoms, R 2 It is connected to the organic boronic acid group through a boron-carbon bond.

[0050] The hydroxyl group in the organic boronic acid group contained in the monoorganic boronic acid and diorganic boronic acid can form an ester with an alcohol in the same manner as the hydroxyl group in the boric acid. The following formula (III) is an example of an organic boronic acid monoester group obtained by reacting one molecule of alcohol (R-OH) with an organic boronic acid group. Here, when the organic boronic acid group is bonded to the hydroxyl group of PVA (A), R in the following formula (III) is a PVA chain, and a carbon-containing group is bonded to the PVA chain via a boron atom.

[0051] [Chemistry 5]

[0052]

[0053] The following structural formula (IV) is an example of an organic boronic acid diester group obtained by reacting two molecules of alcohol (R-OH) with an organic boronic acid group. Here, when the organic boronic acid group is bonded to the hydroxyl group of PVA, both R in the structural formula (IV) are PVA chains.

[0054] [Chemistry 6]

[0055]

[0056] Monoorganic boric acid has two hydroxyl groups that can react with the hydroxyl groups of PVA to form esters, and the PVA chains are moderately crosslinked. The crosslinking is thermally stable, so the shrinkage force of the polarizing film at high temperatures becomes smaller. As a result, the warping of LCD panels and OLED panels obtained using polarizing films at high temperatures is suppressed. In addition, it can be considered that by introducing a ring structure into the PVA chain through intramolecular crosslinking, the movement of the PVA chain is reduced, which also helps to reduce the shrinkage force of the polarizing film.

[0057] The diorganoboric acid has 4 hydroxyl groups that can react with the hydroxyl groups of PVA to form esters, and the PVA chains are firmly cross-linked. The cross-linking is thermally stable, so the shrinkage force of the polarizing film at high temperatures becomes smaller. As a result, the warping of the LCD panel and OLED panel obtained using the polarizing film at high temperatures is suppressed. In addition, it can be considered that the PVA chains are firmly cross-linked, thereby reducing the mobility of the PVA chains under high temperature and high humidity, thereby improving the moisture and heat resistance of the polarizing film.

[0058] In the above formula (I), R 1 It is a monovalent aliphatic group having 1 to 20 carbon atoms. 1 The length of R is appropriate, thereby controlling the solubility of the boron-containing compound (B) in water and the reactivity with the hydroxyl group of PVA (A). 1The number of carbon atoms in R is preferably 10 or less, more preferably 6 or less, and further preferably 5 or less. On the other hand, from the viewpoint of particularly excellent balance between the optical properties and the shrinkage force of the polarizing film, R 1 The number of carbon atoms in is preferably 2 or more, more preferably 3 or more.

[0059] In the above formula (I), as long as R 1 is a monovalent aliphatic group, and R 1 It can be connected to the organic boronic acid group through a boron-carbon bond. 1 It can be a saturated aliphatic group or an unsaturated aliphatic group, and the former is preferred. 1 A saturated aliphatic group is used, thereby suppressing the coloring of the obtained polarizing film and improving the durability. 1 It is a saturated aliphatic group, which improves the orientation of the dichroic pigment and further improves the optical performance. It should be noted that the unsaturated aliphatic group refers to an aliphatic group having a structure containing a carbon-carbon double bond, a carbon-carbon triple bond, a carbon-oxygen double bond, a carbon-nitrogen double bond, a nitrogen-nitrogen double bond, a carbon-sulfur double bond, and a multi-bond structure with a bonding order of 2 or more, and the saturated aliphatic group refers to an aliphatic group having only a single bond structure. 1Examples of the monoorganoboric acid which is a saturated aliphatic group include methylboric acid, ethylboric acid, propylboric acid, butylboric acid, pentylboric acid, hexylboric acid, heptylboric acid, octylboric acid, nonylboric acid, decylboric acid, undecylboric acid, dodecylboric acid, tridecylboric acid, tetradecylboric acid, pentadecylboric acid, hexadecylboric acid, heptadecylboric acid, octadecylboric acid, nonadecylboric acid, eicosaneboric acid and isomers thereof; cyclopropylboric acid, cyclobutylboric acid, cyclopentylboric acid, cyclohexylboric acid, cycloheptylboric acid, cyclooctylboric acid, cyclononylboric acid, cyclodecylboric acid, cycloundecylboric acid, cyclododecylboric acid, cyclotridecylboric acid , cyclotetradecylboric acid, cyclopentadecylboric acid, cyclohexadecylboric acid, cycloheptadecylboric acid, cyclooctadecylboric acid, cyclononadecylboric acid, cycloeicosaneboric acid and isomers thereof; 2-oxa-propylboric acid, 2-oxa-butylboric acid, 2-oxa-hexylboric acid, 2-oxa-heptylboric acid, 2-oxa-octylboric acid, 2-oxa-nonylboric acid, 2-oxa-decylboric acid, 2-oxa-undecylboric acid, 2-oxa-dodecylboric acid, 2-oxa-tridecylboric acid, 2-oxa-tetradecylboric acid, 2-oxa-pentadecylboric acid, 2-oxa-hexadecylboric acid, 2-oxa-heptadecylboric acid, 2-Oxa-octadecylboric acid, 2-Oxa-nonadecanylboric acid, 2-Oxa-eicosaneboric acid and their isomers; 2-Aza-propylboric acid, 2-Aza-butylboric acid, 2-Aza-hexylboric acid, 2-Aza-heptylboric acid, 2-Aza-octylboric acid, 2-Aza-nonylboric acid, 2-Aza-decylboric acid, 2-Aza-undecylboric acid, 2-Aza-dodecylboric acid, 2-Aza-tridecylboric acid, 2-Aza-tetradecylboric acid, 2-Aza-pentadecanylboric acid, 2-Aza-hexadecylboric acid, 2-Aza-heptadecylboric acid, 2-Aza-octadecylboric acid, 2-Aza-nonadecanylboric acid Boric acid, 2-aza-eicosaneboric acid and isomers thereof; 2-phospha-propylboric acid, 2-phospha-butylboric acid, 2-phospha-hexylboric acid, 2-phospha-heptylboric acid, 2-phospha-octylboric acid, 2-phospha-nonylboric acid, 2-phospha-decylboric acid, 2-phospha-undecylboric acid, 2-phospha-dodecylboric acid, 2-phospha-tridecylboric acid, 2-phospha-tetradecylboric acid, 2-phospha-pentadecylboric acid, 2-phospha-hexadecylboric acid, 2-phospha-heptadecylboric acid, 2-phospha-octadecylboric acid, 2-phospha-nonadecylboric acid, 2-phospha-eicosaneboric acid and isomers thereof;2-thia-propylboric acid, 2-thia-butylboric acid, 2-thia-hexylboric acid, 2-thia-heptylboric acid, 2-thia-octylboric acid, 2-thia-nonylboric acid, 2-thia-decylboric acid, 2-thia-undecylboric acid, 2-thia-dodecylboric acid, 2-thia-tridecylboric acid, 2-thia-tetradecylboric acid, 2-thia-pentadecylboric acid, 2-thia-hexadecylboric acid, 2-thia-heptadecylboric acid, 2-thia-octadecylboric acid, 2-thia-nonadecylboric acid, 2-thia-eicosaneboric acid and isomers thereof. In addition, as compounds that can be converted into the exemplified monoorganoboric acid in the presence of water, salts of the monoorganoboric acid and the like can be cited. ;

[0060] R 1 It may be an aliphatic hydrocarbon group, and may contain heteroatoms such as oxygen, nitrogen, sulfur, and halogen. 1 It is preferably an aliphatic hydrocarbon group containing no heteroatoms. As the aliphatic hydrocarbon group, it is preferably a straight-chain aliphatic hydrocarbon group without branches. It is believed that the adsorption to the PVA film becomes good, and the effect of improving the optical properties and reducing the shrinkage force is further improved. It should be noted that as R 1 Specific examples of the organic boronic acid which is an aliphatic hydrocarbon group include methylboric acid, ethylboric acid, propylboric acid, butylboric acid, pentylboric acid, hexylboric acid, heptylboric acid, octylboric acid, nonylboric acid, decylboric acid, undecylboric acid, dodecylboric acid, tridecylboric acid, tetradecylboric acid, pentadecylboric acid, hexadecylboric acid, heptadecylboric acid, octadecylboric acid, nonadecylboric acid, eicosaneboric acid and isomers thereof; cyclopropylboric acid, cyclobutylboric acid, cyclopentylboric acid, cyclohexylboric acid, cycloheptylboric acid, cyclooctylboric acid, cyclononylboric acid, cyclodecylboric acid, cycloundecylboric acid, cyclododecylboric acid, cyclotridecylboric acid, cyclotetradecylboric acid, cyclopentadecylboric acid, cyclohexadecylboric acid, cycloheptadecylboric acid, cyclooctadecylboric acid, cyclononadecylboric acid, cycloeicosaneboric acid and isomers thereof. Examples of the compound that can be converted into the exemplified monoorganoboric acid in the presence of water include salts of the monoorganoboric acid.

[0061] Specifically, R 1 An alkyl group is preferred, and an alkyl group represented by the following formula (V) is more preferred.

[0062] [Chemistry 7]

[0063] CnH2n+1(V)

[0064] In the above formula (V), n is 1 to 20. n is preferably 10 or less, more preferably 6 or less, and even more preferably 5 or less. On the other hand, n is preferably 2 or more, and more preferably 3 or more.

[0065] From the viewpoint of obtaining a polarizing film with a smaller shrinkage force at high temperature and excellent optical performance, R 1 A saturated aliphatic hydrocarbon group having 2 to 5 carbon atoms is particularly preferred. If the number of carbon atoms is less than 2, the bonding stability between PVA (A) and the boron-containing compound (B) is reduced, and thus the effect of reducing the shrinkage force and the effect of improving the optical properties may become insufficient. If the number of carbon atoms is greater than 5, the boron-containing compound (B) is more likely to be present on the surface of the polarizing film, and thus the effect of reducing the shrinkage force and the effect of improving the optical properties may become insufficient.

[0066] As the monoorganic boric acid shown in the above-mentioned formula (I), specifically, methylboric acid, ethylboric acid, propylboric acid, butylboric acid, amylboric acid, hexylboric acid, heptylboric acid, octylboric acid, nonylboric acid, decylboric acid, undecylboric acid, dodecylboric acid, tridecylboric acid, tetradecylboric acid, pentadecylboric acid, hexadecylboric acid, heptadecanylboric acid, octadecylboric acid, nonadecanylboric acid, eicosaneboric acid and their isomers etc. can be illustrated. From the viewpoint that the adsorptivity of PVA film is good, the effect of improving optical performance is high, particularly preferably propylboric acid, butylboric acid and amylboric acid. In addition, as the compound that can be converted into the monoorganic boric acid shown in the above-mentioned formula (I) in the presence of water, the salt of this monoorganic boric acid, monoorganic boric acid ester etc. can be enumerated.

[0067] In the above formula (II), R 2 It is a divalent aliphatic group having 1 to 20 carbon atoms. 2 The length of R is appropriate, thereby controlling the solubility of the boron-containing compound (C) in water and the reactivity with the hydroxyl group of PVA (A). 2 The number of carbon atoms in R is preferably 10 or less, more preferably 8 or less, further preferably 6 or less, and particularly preferably 5 or less. On the other hand, from the viewpoint of further improving the moisture and heat resistance of the polarizing film, R 2 The number of carbon atoms in is preferably 3 or more, more preferably 4 or more.

[0068] In the above formula (II), as long as R 2 is a divalent aliphatic group, and R 2 It can be connected to the organic boronic acid group through a boron-carbon bond. 2 It can be a saturated aliphatic group or an unsaturated aliphatic group, and the former is preferred. 2 is a saturated aliphatic group, thereby suppressing the coloring of the obtained polarizing film. 2 The saturated aliphatic group improves the diffusibility of the boron-containing compound (C) in the polarizing film, and further improves the effect of improving the moisture and heat resistance and the effect of reducing the shrinkage force.

[0069] R 2 It may be an aliphatic hydrocarbon group, and may contain heteroatoms such as oxygen, nitrogen, sulfur, and halogen. 2 Preferably, the aliphatic hydrocarbon group does not contain heteroatoms. As the aliphatic hydrocarbon group, preferably, a straight-chain aliphatic hydrocarbon group without branches is used. It can be considered that the adsorption of the boron-containing compound (C) to the PVA film becomes good, and the effect of improving the moisture and heat resistance and reducing the shrinkage force is further improved.

[0070] Specifically, R 2 An alkylene group is preferred, and an alkylene group represented by the following formula (VI) is more preferred.

[0071] [Chemistry 8]

[0072] CnH2n(VI)

[0073] In the above formula (VI), n is 1 to 20. n is preferably 10 or less, more preferably 8 or less, further preferably 6 or less, and particularly preferably 5 or less. On the other hand, n is preferably 3 or more, more preferably 4 or more.

[0074] From the viewpoint of obtaining a polarizing film having excellent resistance to moisture and heat, R 2 Particularly preferred are saturated aliphatic hydrocarbon groups having 3 to 5 carbon atoms. When the number of carbon atoms is less than 3, the crosslinking efficiency between PVA chains based on the boron-containing compound (C) is reduced, and therefore, the effect of improving moisture and heat resistance is sometimes insufficient. When the number of carbon atoms is greater than 5, the boron-containing compound (C) is more likely to be present on the surface of the polarizing film, and therefore, the effect of improving moisture and heat resistance is sometimes insufficient. In addition, the water solubility of the boron-containing compound (C) is also reduced, and therefore, the boron-containing compound (C) is easily precipitated on the surface of the polarizing film.

[0075] As the diorganoboric acid represented by the above formula (II), specifically, methanediboric acid, ethanediboric acid, propanediboric acid, butanediboric acid, pentanediboric acid, hexanediboric acid, heptanediboric acid, octanediboric acid, nonanediboric acid, decanediboric acid, undecanediboric acid, dodecanediboric acid, tridecanediboric acid, tetradecanediboric acid, pentadecanediboric acid, hexadecanediboric acid, heptadecanediboric acid, octadecanediboric acid, nonadecanediboric acid, eicosanediboric acid and their isomers can be exemplified. From the viewpoint of good adsorption to the aforementioned polarizing film and high effect of improving moisture and heat resistance, propanediboric acid, butanediboric acid and pentanediboric acid are particularly preferred. In addition, as compounds that can be converted into the diorganoboric acid represented by the above formula (II) in the presence of water, salts of the diorganoboric acid, diorganoboric acid esters and the like can be cited.

[0076] The mass ratio (B / C) of the boron element derived from the boron-containing compound (B) to the boron element derived from the boron-containing compound (C) in the polarizing film of the present invention needs to be 4.0 to 8.0. By adjusting the mass ratio (B / C) to this range, a polarizing film with excellent shrinkage force and moisture and heat resistance can be obtained. On the other hand, if the mass ratio (B / C) deviates from the above range and the PVA film excessively adsorbs either the boron-containing compound (B) or the boron-containing compound (C), the excessively adsorbed boron-containing compound will hinder the effect of the other boron-containing compound, and therefore, any of the shrinkage force or moisture and heat resistance becomes insufficient. The mass ratio (B / C) is preferably greater than 5. On the other hand, the mass ratio (B / C) is preferably less than 7, more preferably less than 6.5.

[0077] The content of boron element derived from the boron-containing compound (C) in the polarizing film is 0.05 to 0.3 parts by mass or less relative to 100 parts by mass of PVA (A). When the content of the boron-containing compound (C) is less than 0.05 parts by mass, the effect of improving moisture and heat resistance becomes insufficient. The boron element content is preferably 0.07 parts by mass or more, and more preferably 0.08 parts by mass or more. On the other hand, when the content of boron element derived from the boron-containing compound (C) is greater than 0.3 parts by mass, the reduction in shrinkage force becomes insufficient, although the reason is unclear. In addition, a long processing time, processing at high temperature, etc. may be required, and productivity may be reduced. Therefore, the boron element content is preferably 0.2 parts by mass or less. The boron element content derived from the boron-containing compound (B) and the boron-containing compound (C) in the polarizing film can be increased by 1 It was obtained by H-NMR measurement.

[0078] The content of boron element derived from the boron-containing compound (B) in the polarizing film is appropriately determined according to the above-mentioned mass ratio (B / C) and the content of boron element derived from the boron-containing compound (C), and is not particularly limited. It is preferably 0.1 to 2.0 parts by mass relative to 100 parts by mass of PVA (A). When the aforementioned boron element content is less than 0.1 parts by mass, the reduction in shrinkage force may become insufficient. The aforementioned boron element content is more preferably 0.4 parts by mass or more. On the other hand, when the aforementioned boron element content is greater than 2.0 parts by mass, the effect of the boron-containing compound (C) is hindered, and the moisture and heat resistance may become insufficient. The aforementioned boron element content is more preferably 1.6 parts by mass or less, and further preferably 1.4 parts by mass or less.

[0079] The polarizing film of the present invention may further contain boric acid. As a result, the optical performance is sometimes improved. At this time, the total boron content in the polarizing film is preferably 0.2% by mass or more. Here, the total boron content refers to the total amount of boron elements derived from boron-containing compounds (B) and boron-containing compounds (C), boron elements derived from boric acid, and boron elements derived from boron-containing compounds other than boron-containing compounds (B), boron-containing compounds (C) and boric acid contained in the polarizing film. On the other hand, when the total boron content in the polarizing film is too much, the shrinkage force of the polarizing film may increase. The total boron content in the polarizing film is generally 5.5% by mass or less, preferably 5.0% by mass or less, more preferably 4.5% by mass or less, and further preferably 4.0% by mass or less. The total boron content in the polarizing film can be obtained by ICP emission analysis, etc.

[0080] The degree of polymerization of PVA (A) contained in the polarizing film of the present invention is preferably in the range of 1,500 to 6,000, more preferably in the range of 1,800 to 5,000, and further preferably in the range of 2,000 to 4,000. By setting the degree of polymerization to 1,500 or more, the durability of the polarizing film obtained by uniaxially stretching the film can be improved. On the other hand, by setting the degree of polymerization to 6,000 or less, it is possible to suppress an increase in manufacturing costs, poor passability of the steps during film formation, etc. It should be noted that the degree of polymerization of PVA (A) in this specification refers to the average degree of polymerization measured in accordance with the description of JIS K6726-1994.

[0081] From the viewpoint of water resistance of the polarizing film obtained by uniaxially stretching the film, the saponification degree of the PVA (A) contained in the polarizing film of the present invention is preferably 95 mol% or more, more preferably 96 mol% or more, and further preferably 98 mol% or more. It should be noted that the saponification degree of PVA in this specification refers to: the amount of PVA that can be converted into vinyl alcohol units (-CH 2 The total number of moles of the structural unit (typically vinyl ester unit) of -CH(OH)-) and the vinyl alcohol unit, and the ratio (mol %) of the number of moles of the vinyl alcohol unit. The saponification degree can be measured according to the description of JIS K6726-1994.

[0082] The method for producing PVA (A) used in the present invention is not particularly limited. For example, a method in which the vinyl ester unit of a polyvinyl ester obtained by polymerization of a vinyl ester monomer is converted into a vinyl alcohol unit can be cited. The vinyl ester monomer used in the production of PVA (A) is not particularly limited, and for example, vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, etc. can be cited. From an economic point of view, vinyl acetate is preferred.

[0083] In addition, the PVA (A) used in the present invention may be a substance obtained by converting a vinyl ester unit of a vinyl ester copolymer obtained by copolymerizing a vinyl ester monomer with other monomers copolymerizable therewith into a vinyl alcohol unit. Examples of other monomers copolymerizable with the vinyl ester monomer include α-olefins having 2 to 30 carbon atoms such as ethylene, propylene, 1-butene, and isobutylene; (meth)acrylic acid or its salt; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, (meth)acrylamide propanesulfonic acid or its salt, (meth)acrylic acid esters such as propanesulfonic acid ester ... (Meth)acrylamide derivatives such as (methyl)acrylamide propyl dimethylamine or its salt, N-hydroxymethyl (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, isopropyl vinyl ether, n-butyl vinyl ether, isobutyl vinyl ether, tert-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether; vinyl cyanide such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salt, ester or anhydride; itaconic acid or its salt, ester or anhydride; vinyl silyl compounds such as vinyltrimethoxysilane; unsaturated sulfonic acid, etc. The above-mentioned vinyl ester copolymer may have structural units derived from one or more of the above-mentioned other monomers. The other monomers may be present in the reaction vessel before the vinyl ester monomer is subjected to the polymerization reaction, or may be added to the reaction vessel during the polymerization reaction. From the viewpoint of polarization performance, the content of the units derived from the other monomers is preferably 10 mol% or less, more preferably 5 mol% or less, and further preferably 2 mol% or less, relative to the molar number of all structural units constituting PVA (A).

[0084] From the viewpoint of being able to stretch at a higher temperature while improving stretchability, reducing the occurrence of failures such as stretching fracture, and further improving the productivity of the polarizing film, ethylene is preferably used as a monomer that can be copolymerized with the above-mentioned vinyl ester monomer. When PVA (A) contains ethylene units, from the viewpoints of stretchability, stretchable temperature, etc. as described above, the content of ethylene units is preferably 1 to 10 mol%, more preferably 2 to 6 mol% relative to the number of moles of all structural units constituting PVA (A).

[0085] The PVA film used in the manufacture of the polarizing film of the present invention may contain a plasticizer in addition to the above-mentioned PVA (A). As a preferred plasticizer, polyols may be mentioned, and as specific examples, ethylene glycol, glycerol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, etc. may be mentioned. Furthermore, one or more of these plasticizers may be included. Among these, glycerol is preferred from the perspective of improving the effect of stretchability.

[0086] The content of the plasticizer in the PVA film used in the manufacture of the polarizing film of the present invention is preferably in the range of 1 to 20 parts by mass, more preferably in the range of 3 to 17 parts by mass, and further preferably in the range of 5 to 15 parts by mass relative to 100 parts by mass of PVA (A). By making the content 1 part by mass or more, the stretchability of the film is improved. On the other hand, by making the content 20 parts by mass or less, it is possible to prevent the film from becoming too soft and reducing the handling properties.

[0087] The PVA film used in the manufacture of the polarizing film of the present invention may further contain fillers, processing stabilizers such as copper compounds, weathering stabilizers, colorants, ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, other thermoplastic resins, lubricants, fragrances, defoamers, deodorants, extenders, stripping agents, mold release agents, reinforcing agents, crosslinking agents, mildew inhibitors, preservatives, crystallization rate retarders and other additives other than PVA (A) and plasticizers as needed. The content of other additives in the aforementioned PVA film is usually 10% by mass or less, preferably 5% by mass or less.

[0088] The swelling degree of the PVA film used in the manufacture of the polarizing film of the present invention is preferably in the range of 160 to 240%, more preferably in the range of 170 to 230%, and particularly preferably in the range of 180 to 220%. By setting the swelling degree to 160% or more, it is possible to suppress the extreme progress of crystallization and stably stretch to a high ratio. On the other hand, by setting the swelling degree to 240% or less, dissolution during stretching is suppressed, and stretching is possible even under higher temperature conditions.

[0089] The thickness of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited, and is generally 1 to 100 μm, preferably 5 to 60 μm, and particularly preferably 10 to 45 μm. If the aforementioned PVA film is too thin, there is a tendency for stretching fracture to occur during the uniaxial stretching treatment used to manufacture the polarizing film. In addition, if the aforementioned PVA film is too thick, there is a tendency for uneven stretching to occur during the uniaxial stretching treatment used to manufacture the polarizing film, and there is a tendency for the shrinkage force of the manufactured polarizing film to become larger.

[0090] The width of the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited and can be determined according to the purpose of the manufactured polarizing film, etc. In recent years, from the perspective of promoting the large screen of liquid crystal televisions and liquid crystal displays, if the width of the PVA film used in the manufacture of the polarizing film is set to 3m or more, it is suitable for these uses. On the other hand, if the width of the PVA film used in the manufacture of the polarizing film is too large, it is easy to become difficult to uniformly perform uniaxial stretching when the polarizing film is manufactured using a practical device, so the width of the PVA film used in the manufacture of the polarizing film is preferably 10m or less.

[0091] The method for manufacturing the PVA film used in the manufacture of the polarizing film of the present invention is not particularly limited, and it is preferred to adopt a manufacturing method that makes the thickness and width of the film after film formation uniform. For example, the following film-making stock solution can be used for manufacturing: a film-making stock solution obtained by dissolving PVA (A) in a liquid medium and further dissolving one or more of the aforementioned plasticizer, the aforementioned other additives, and the surfactant described below as needed; a film-making stock solution containing PVA (A) and further containing one or more of the plasticizer, other additives, surfactants, and liquid medium as needed, and the PVA (A) is melted. When the film-making stock solution contains at least one of the plasticizer, other additives, and surfactants, these components are preferably uniformly mixed.

[0092] Examples of the liquid medium used in the preparation of the membrane stock solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerol, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, and diethylenetriamine. One or more of these can be used. Among them, water is preferred from the viewpoint of environmental burden and recyclability.

[0093] The volatility of the film-forming stock solution (the proportion of volatile components such as the liquid medium removed by volatilization and evaporation during film formation in the film-forming stock solution) also varies depending on the film-forming method, film-forming conditions, etc., and is generally preferably in the range of 50 to 95% by mass, and more preferably in the range of 55 to 90% by mass. By making the volatility of the film-forming stock solution 50% by mass or more, the viscosity of the film-forming stock solution will not be too high, and filtration and degassing during the preparation of the film-forming stock solution will be smoothly performed, making it easy to produce a film with few foreign matter and defects. On the other hand, by making the volatility of the film-forming stock solution 95% by mass or less, the concentration of the film-forming stock solution will not be too low, and it is easy to produce a film industrially.

[0094] The film-forming stock solution preferably contains a surfactant. By containing a surfactant, the film-forming property is improved, the occurrence of uneven film thickness is suppressed, and the film is easily peeled off from the metal roll or belt used in the film-forming. In the case of manufacturing a PVA film from a film-forming stock solution containing a surfactant, the film can contain a surfactant. The type of the above-mentioned surfactant is not particularly limited, and from the viewpoint of peelability from a metal roll or belt, an anionic surfactant or a nonionic surfactant is preferably used.

[0095] Suitable anionic surfactants include, for example, carboxylic acid-type surfactants such as potassium laurate; sulfate-type surfactants such as polyoxyethylene lauryl ether sulfate, sodium alkyl sulfate, potassium alkyl sulfate, ammonium alkyl sulfate, triethanolamine alkyl sulfate, sodium polyoxyethylene alkyl ether sulfate, sodium polyoxypropylene alkyl ether sulfate, sodium polyoxyethylene alkylphenyl ether sulfate, and octyl sulfate; sulfonic acid-type surfactants such as sodium alkyl sulfonate, potassium alkyl sulfonate, ammonium alkyl sulfonate, triethanolamine alkyl sulfonate, sodium alkylbenzene sulfonate, disodium dodecyl diphenyl ether disulfonate, sodium alkylnaphthalene sulfonate, disodium alkyl sulfosuccinate, disodium polyoxyethylene alkyl sulfosuccinate, and dodecylbenzene sulfonate; phosphate-type surfactants such as sodium alkyl phosphate, potassium alkyl phosphate, ammonium alkyl phosphate, triethanolamine alkyl phosphate, sodium polyoxyethylene alkyl ether phosphate, sodium polyoxypropylene alkyl ether phosphate, and sodium polyoxyethylene alkylphenyl ether phosphate.

[0096] As the nonionic surfactant, suitable ones include, for example, alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkylamine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether, etc.

[0097] These surfactants may be used alone or in combination of two or more.

[0098] When the film-forming stock solution contains a surfactant, its content is preferably in the range of 0.01 to 0.5 parts by mass, more preferably in the range of 0.02 to 0.3 parts by mass, and particularly preferably in the range of 0.05 to 0.2 parts by mass, relative to 100 parts by mass of PVA (A) contained in the film-forming stock solution. By making the content 0.01 parts by mass or more, the film-forming property and the peeling property are further improved. On the other hand, by making the content 0.5 parts by mass or less, it is possible to suppress the surfactant from seeping out on the surface of the PVA film, causing blocking and reduced handling properties.

[0099] As a method for using the above-mentioned film-making stock solution to make a PVA film, for example, a cast film-making method, an extrusion film-making method, a wet film-making method, a gel film-making method, etc. can be cited. These film-making methods can only adopt one kind, and two or more kinds can also be combined. From the viewpoint of obtaining a PVA film with uniform thickness and width and good physical properties, among these film-making methods, preferably a cast film-making method and an extrusion film-making method. The PVA film obtained by film-making can be dried and heat-treated as needed.

[0100] As an example of a specific method for manufacturing the PVA film used in the manufacture of the polarizing film of the present invention, the following method can be preferably used industrially: for example, using a T-slit die, a hopper plate, an I-die, a lip coater die, etc., the above-mentioned film-making stock solution is uniformly sprayed or cast on the circumference of the rotating and heated first roller (or belt) located on the upstream side, and the volatile components are evaporated from one side of the film sprayed or cast on the circumference of the first roller (or belt) to dry, and then, it is further dried on the circumference of one or more rotating and heated rollers arranged on its downstream side, or it is further dried by passing it through a hot air drying device, and then it is wound up using a winding device. Drying using a heated roller and drying using a hot air drying device can be appropriately combined. In addition, by forming a layer containing PVA (A) on one surface of a substrate film composed of a single resin layer, a multi-layer PVA film can also be produced.

[0101] There is no particular restriction on the method for manufacturing the polarizing film of the present invention. A suitable manufacturing method is a method for manufacturing the following polarizing film: In a method for manufacturing a polarizing film that includes a dyeing treatment of dyeing a PVA film with a dichroic pigment and a stretching treatment of uniaxially stretching the film, there are: a treatment of immersing the film in an aqueous solution containing a boron-containing compound (B) and a treatment of immersing the film in an aqueous solution containing a boron-containing compound (C). At this time, there can be cited a method of subjecting the PVA film to a dyeing treatment and a uniaxial stretching treatment, and further subjecting the PVA film to a swelling treatment, a boric acid cross-linking treatment, a fixing treatment, a washing treatment, a drying treatment, a heat treatment, and the like as needed. In this case, the order of the swelling treatment, the dyeing treatment, the boric acid cross-linking treatment, the uniaxial stretching treatment, the fixing treatment, and the like is not particularly limited, and one or more treatments may be performed simultaneously. In addition, one or more of the treatments may be performed two or more times.

[0102] The swelling treatment can be performed by immersing the PVA film in water. The temperature of the water in which the film is immersed is preferably in the range of 20 to 40°C, more preferably in the range of 22 to 38°C, and further preferably in the range of 25 to 35°C. In addition, the time of immersion in water is, for example, preferably in the range of 0.1 to 5 minutes, and more preferably in the range of 0.2 to 3 minutes. It should be noted that the water in which the film is immersed is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or may be a mixture of water and a hydrophilic medium.

[0103] The dyeing treatment can be carried out by contacting the PVA film with a dichroic pigment. As a dichroic pigment, an iodine-based pigment and a dichroic dye are generally used. As the period of the dyeing treatment, it can be any stage before the uniaxial stretching treatment, during the uniaxial stretching treatment, and after the uniaxial stretching treatment. The dyeing treatment is generally carried out by immersing the PVA film in a solution (especially an aqueous solution) containing iodine-potassium iodide as a dyeing bath or a solution (especially an aqueous solution) containing a plurality of dichroic dyes. The concentration of iodine in the dyeing bath is preferably in the range of 0.01 to 0.5% by mass, and the concentration of potassium iodide is preferably in the range of 0.01 to 10% by mass. In addition, the temperature of the dyeing bath is preferably set to 20 to 50°C, especially 25 to 40°C. Suitable dyeing time is 0.2 to 5 minutes. In the case of using a dichroic dye, the dichroic dye is preferably an aqueous dye. In addition, the dye concentration in the dyeing bath is preferably 0.001 to 10% by mass. In addition, dyeing auxiliaries can be used as needed, and inorganic salts such as sodium sulfate, surfactants, etc. can be used. When sodium sulfate is used, the content is preferably 0.1 to 10% by mass. The dyeing temperature is preferably 30 to 80° C. Specific dichroic dyes include CI Direct Yellow 28, CI Direct Orange 39, CI Direct Yellow 12, CI Direct Yellow 44, CI Direct Orange 26, CI Direct Orange 71, CI Direct Orange 107, CI Direct Red 2, CI Direct Red 31, CI Direct Red 79, CI Direct Red 81, CI Direct Red 247, CI Direct Green 80, and CI Direct Green 59. Dichroic dyes developed for the manufacture of polarizing plates are preferred.

[0104] The PVA film may also be subjected to a boric acid crosslinking treatment. In this case, it is possible to more effectively prevent the PVA (A) from dissolving in water during wet stretching at high temperature. From this viewpoint, the boric acid crosslinking treatment is preferably performed before the uniaxial stretching treatment. The boric acid crosslinking treatment may be performed by immersing the PVA film in an aqueous solution containing a boric acid crosslinking agent. As the boric acid crosslinking agent, one or more of boron-containing inorganic compounds such as borate salts such as boric acid and borax may be used. The concentration of the boric acid crosslinking agent in the aqueous solution containing the boric acid crosslinking agent is preferably in the range of 0.1 to 6.0% by mass. The concentration of the boric acid crosslinking agent is more preferably 0.2% by mass or more. In addition, it is more preferably 4.0% by mass or less. By making the concentration of the boric acid crosslinking agent within the above range, stretchability can sometimes be improved. When the concentration of the boric acid crosslinking agent is too high, it is sometimes difficult to contain the boron-containing compound (B) and the boron-containing compound (C) in the subsequent steps, so it is better that the concentration is not too high. The aqueous solution containing the boric acid crosslinking agent may contain auxiliary agents such as potassium iodide. The temperature of the aqueous solution containing the boric acid crosslinking agent is preferably within a range of 20 to 50°C, particularly preferably within a range of 25 to 40°C.

[0105] In addition to the uniaxial stretching treatment described later, the PVA film can be stretched (pre-stretched) in or during the above-mentioned treatments. In this way, from the viewpoint of the optical properties of the resulting polarizing film, the total stretching ratio (the ratio obtained by multiplying the stretching ratios in each treatment) of the pre-stretching performed earlier than the uniaxial stretching treatment is preferably 1.5 times or more, more preferably 2.0 times or more, and further preferably 2.5 times or more based on the original length of the raw PVA film before stretching. On the other hand, the total stretching ratio is preferably 4.0 times or less, more preferably 3.5 times or less. As the stretching ratio in the swelling treatment, it is preferably 1.05 to 2.5 times. As the stretching ratio in the dyeing treatment, it is preferably 1.1 to 2.5 times. As the stretching ratio in the boric acid cross-linking treatment, it is preferably 1.1 to 2.5 times.

[0106] The uniaxial stretching treatment can be carried out by either a wet stretching method or a dry stretching method. In the case of the wet stretching method, stretching is performed in an aqueous solution. It can also be stretched in the above-mentioned dyeing bath, a boric acid aqueous solution, etc. In addition, in the case of the dry stretching method, the uniaxial stretching treatment can be carried out at room temperature, the uniaxial stretching treatment can be carried out while heating, and the PVA film after absorbing water can also be used for uniaxial stretching in the air. Among these, the wet stretching method is preferred, and the uniaxial stretching treatment is more preferably carried out in an aqueous solution containing boric acid. The boric acid concentration in the boric acid aqueous solution is preferably in the range of 0.5 to 6% by mass, and more preferably in the range of 1 to 5% by mass. In addition, the boric acid aqueous solution may contain potassium iodide, and its concentration is preferably set in the range of 0.01 to 10% by mass. The stretching temperature in the uniaxial stretching treatment is preferably 30°C or more, more preferably 40°C or more, and more preferably 50°C or more. On the other hand, the stretching temperature is preferably 90°C or less, more preferably 80°C or less, and more preferably 70°C or less. In addition, as the stretching ratio in the uniaxial stretching treatment, it is preferably 2.0 to 4.0 times. From the viewpoint of the optical properties of the obtained polarizing film, the stretching ratio is more preferably 2.2 times or more. On the other hand, the stretching ratio is more preferably 3.5 times or less. In addition, from the viewpoint of the optical properties of the obtained polarizing film, the total stretching ratio before the fixing treatment described later is preferably 5 times or more, more preferably 5.5 times or more based on the original length of the raw material PVA film before stretching. There is no particular upper limit on the stretching ratio, and the stretching ratio is preferably 8 times or less.

[0107] The direction of the uniaxial stretching treatment when the long PVA film is subjected to uniaxial stretching treatment is not particularly limited. The uniaxial stretching treatment in the long strip direction, the transverse uniaxial stretching treatment, and the so-called oblique stretching treatment can be adopted. From the viewpoint of obtaining a polarizing film with excellent optical properties, the uniaxial stretching treatment in the long strip direction is preferred. The uniaxial stretching treatment in the long strip direction can be carried out by using a stretching device having a plurality of rollers parallel to each other and changing the peripheral speed between the rollers. On the other hand, the transverse uniaxial stretching treatment can be carried out using a tenter-type stretching machine.

[0108] When manufacturing a polarizing film, in order to make the adsorption of dichroic pigments (iodine-based pigments, etc.) on the PVA film firm, it is preferred to perform a fixing treatment after the uniaxial stretching treatment. As a fixing treatment bath used in the fixing treatment, an aqueous solution containing a boron-containing compound (B) or a boron-containing compound (C) can be suitably used. In addition, boric acid, iodine compounds, metal compounds, etc. can be further added to the fixing treatment bath as needed. The temperature of the fixing treatment bath is preferably 10 to 80°C. The stretching ratio in the fixing treatment is preferably 1.3 times or less, more preferably 1.2 times or less, and further preferably less than 1.1 times.

[0109] In the above-mentioned manufacturing method, the PVA film is immersed in an aqueous solution containing a boron-containing compound (B) and an aqueous solution containing a boron-containing compound (C), thereby allowing the film to adsorb the boron-containing compound (B) and the boron-containing compound (C). At this time, by immersing the PVA film in an aqueous solution containing both the boron-containing compound (B) and the boron-containing compound (C), the boron-containing compound (B) and the boron-containing compound (C) can be adsorbed on the above-mentioned film in one stage. From the viewpoint of being able to adsorb the boron-containing compound (B) and the boron-containing compound (C) on the above-mentioned film without competition, taking into account the shrinkage reduction effect and the moisture-heat resistance improvement effect, it is preferred to immerse the film in an aqueous solution containing a boron-containing compound (B) and an aqueous solution containing a boron-containing compound (C), respectively.

[0110] At this time, it is more preferred that after the PVA film is immersed in the aqueous solution containing the boron-containing compound (B), the film is immersed in the aqueous solution containing the boron-containing compound (C). If the order of these treatments is reversed, the boron-containing compound (C) will significantly hinder the adsorption of the boron-containing compound (B), so it is possible to reduce the effect of shrinkage force and become insufficient, and the optical performance is reduced. In addition, the boron content of the boron element derived from the boron-containing compound (B) in the PVA film after immersion in the aqueous solution containing the boron-containing compound (B) and before immersion in the aqueous solution containing the boron-containing compound (C) is preferably less than 1.3 parts by mass, particularly preferably less than 1.0 parts by mass. If the aforementioned content is greater than 1.3 parts by mass, the adsorption of the boron-containing compound (C) will be hindered, and it is possible that the resistance to moisture and heat becomes insufficient. On the other hand, if the content of the boron-containing compound (B) is too small, the reduction in shrinkage force becomes insufficient. Therefore, the content of boron element derived from the boron-containing compound (B) in the PVA film after immersion in an aqueous solution containing the boron-containing compound (B) and before immersion in an aqueous solution containing the boron-containing compound (C) is preferably 0.1 parts by mass or more.

[0111] The concentration of the boron-containing compound (B) in the aqueous solution containing the boron-containing compound (B) is preferably 15% by mass or less. When the aforementioned concentration is higher than 15% by mass, a high-density adsorption layer of the boron-containing compound (B) is formed on the surface of the polarizing film in a short time, which may hinder the adsorption of the boron-containing compound (C) to the polarizing film. In addition, the boron-containing compound (B) may be present in a concentrated manner near the surface of the polarizing film, as a result, the optical performance may be reduced. The aforementioned concentration is more preferably 10% by mass or less, further preferably 5.0% by mass or less, particularly preferably 3.5% by mass or less, further preferably 1.5% by mass or less, and most preferably 0.8% by mass or less. On the other hand, the concentration of the boron-containing compound (B) is preferably 0.1% by mass or more.

[0112] The aqueous solution containing the boron-containing compound (B) may contain a boron-containing compound (C) as long as it does not hinder the effect of the present invention. The ratio (C / B) of the concentration [mass %] of the boron-containing compound (C) in the aqueous solution to the concentration [mass %] of the boron-containing compound (B) is preferably 0.1 or less, more preferably 0.01 or less, and further preferably substantially no boron-containing compound (C) is contained. If the ratio (C / B) of the concentration [mass %] is greater than 0.1, the adsorption of the boron-containing compound (B) will be hindered by the boron-containing compound (C), and the effect of reducing the contractile force may become insufficient.

[0113] The concentration of the boron-containing compound (C) in the aqueous solution containing the boron-containing compound (C) is preferably less than 2.0 mass %, more preferably less than 1.5 mass %, and further more preferably less than 0.8 mass %. When the concentration of the aqueous solution of the boron-containing compound (C) is high, the reason is unclear, but sometimes the reduction of the shrinkage force is insufficient. On the other hand, when the concentration of the boron-containing compound (C) is too low, the improvement of the wet heat resistance sometimes becomes insufficient, and the concentration is preferably 0.1 mass % or more, particularly preferably 0.3 mass % or more.

[0114] As long as it does not hinder the effect of the present invention, the aqueous solution containing the boron-containing compound (C) may contain a boron-containing compound (B), and the ratio (B / C) of the concentration [mass %] of the boron-containing compound (B) in the aqueous solution to the concentration [mass %] of the boron-containing compound (C) is preferably less than 1, more preferably less than 0.5, further preferably less than 0.1, and further preferably substantially free of the boron-containing compound (B). When the ratio (B / C) of the concentration [mass %] is greater than 1, the adsorption of the boron-containing compound (C) is hindered by the boron-containing compound (B), and the effect of improving the moisture-heat resistance may become insufficient.

[0115] From the viewpoint of optical performance, the aqueous solution containing a boron-containing compound (B) or a boron-containing compound (C) preferably contains an auxiliary agent of an iodide such as potassium iodide, and the concentration of the iodide is preferably 0.5 to 15% by mass. In addition, the temperature of these aqueous solutions is preferably 10 to 80°C. If the temperature is too low, the boron-containing compound (B) and the boron-containing compound (C) may precipitate in the treatment bath. The temperature of the aqueous solution is more preferably above 15°C, and further preferably above 20°C. On the other hand, if the temperature is too high, it is difficult to industrially manufacture a polarizing film under relatively mild conditions. The temperature of the aqueous solution is more preferably below 70°C, further preferably below 60°C, and particularly preferably below 50°C. The time of immersion in the aqueous solution is preferably 5 to 400 seconds.

[0116] The boron-containing compound (B) and the boron-containing compound (C) can be adsorbed on the PVA film in any step of the dyeing treatment, boric acid cross-linking treatment, uniaxial stretching treatment, and fixing treatment. From the viewpoint of suppressing the breakage of the PVA film during the uniaxial stretching treatment and obtaining a polarizing film with particularly excellent optical properties, it is preferably carried out after the uniaxial stretching treatment, and particularly preferably during the fixing treatment after the uniaxial stretching treatment.

[0117] A suitable manufacturing method for adsorbing the boron-containing compound (B) and the boron-containing compound (C) to the polarizing film during the fixing treatment is to sequentially carry out a swelling treatment, a uniaxial stretching treatment, a fixing treatment using the boron-containing compound (B), and a fixing treatment using the boron-containing compound (C); sequentially carry out a swelling treatment, a boric acid cross-linking treatment, a uniaxial stretching treatment, a fixing treatment using the boron-containing compound (B), and a fixing treatment using the boron-containing compound (C); or sequentially carry out a swelling treatment, a uniaxial stretching treatment, a fixing treatment using the boron-containing compound (B), a fixing treatment using the boron-containing compound (C), and a boric acid cross-linking treatment. Thereafter, further, as needed, one or more treatments selected from a washing treatment, a drying treatment, and a heat treatment may be carried out. On the other hand, it is not preferred to carry out a fixing treatment using the boron-containing compound (C) before the fixing treatment using the boron-containing compound (B). When the fixing treatment is performed in this order, the boron-containing compound (C) is strongly bonded to the hydroxyl group of the PVA film, thereby inhibiting the adsorption of the boron-containing compound (B) to the polarizing film. As a result, the optical performance may be reduced or the reduction of the shrinkage force may become insufficient.

[0118] The washing treatment is generally carried out by immersing the film in distilled water, pure water, aqueous solution, etc. At this time, from the viewpoint of optical performance, it is preferred to use an aqueous solution containing an iodide such as potassium iodide as an auxiliary agent, and the concentration of the iodide is preferably set to 0.5 to 10% by mass. In addition, the temperature of the aqueous solution in the washing treatment is generally 5 to 50°C, preferably 10 to 45°C, and more preferably 15 to 40°C. From an economic viewpoint, it is not preferred that the temperature of the aqueous solution is too low, and if the temperature of the aqueous solution is too high, the optical performance is sometimes reduced.

[0119] The drying conditions are not particularly limited, but the drying is preferably performed at a temperature in the range of 30 to 150° C., particularly preferably 50 to 130° C. Drying at a temperature in the range of 30 to 150° C. makes it easy to obtain a polarizing film having excellent dimensional stability.

[0120] By performing a heat treatment after the drying treatment, the dimensional stability can sometimes be further improved. Here, the heat treatment refers to a treatment in which the polarizing film having a moisture content of 5% or less after the drying treatment is further heated. The conditions for the heat treatment are not particularly limited, and the heat treatment is preferably performed in the range of 60°C to 150°C, and particularly preferably in the range of 70°C to 150°C. When the heat treatment temperature is lower than 60°C, the dimensional stabilization effect may sometimes become insufficient, and when it is higher than 150°C, the polarizing film may suddenly turn red.

[0121] The polarizing film of the present invention obtained in this way has a small shrinkage force at high temperature and excellent resistance to moisture and heat. The shrinkage force of the polarizing film is preferably less than 5N, more preferably less than 4N. In addition, the attenuation coefficient of the PVA-iodine complex in the aforementioned polarizing film is also preferably greater than -0.5, more preferably greater than -0.4. The shrinkage force of the aforementioned polarizing film and the attenuation coefficient of the PVA-iodine complex are measured by the method described in the examples described below.

[0122] The polarizing film of the present invention is usually used as a polarizing plate by laminating an optically transparent and mechanically strong protective film on both sides or one side thereof. As the protective film, a triacetate cellulose (TAC) film, a cellulose acetate-butyrate (CAB) film, an acrylic film, a polyester film, etc. are used. In addition, as an adhesive for lamination, a PVA adhesive, a UV curing adhesive, etc. can be cited.

[0123] The polarizing plate obtained in the above manner may be laminated with a retardation film, a viewing angle enhancement film, a brightness enhancement film, etc. In addition, an acrylic adhesive or the like may be applied to the polarizing plate and then laminated with a glass substrate to be used as a component of an LCD.

[0124] Example

[0125] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited to these examples at all. It should be noted that each measurement or evaluation method used in the following examples and comparative examples is as follows.

[0126] [Measurement of the boron element content derived from the boron-containing compound (B) and the boron-containing compound (C) in the polarizing film containing the boron-containing compound (B) and the boron-containing compound (C)]

[0127] The polarizing film was dissolved in heavy water so that the content thereof became 0.003 mass %, and concentrated by a rotary evaporator so that the content thereof became 0.15 mass %. 1 H-NMR measurement sample. 1H-NMR (manufactured by JEOL Ltd., JNM-AL400: 400 MHz) measurement was performed at 80°C, and the number of accumulations was set to 256. ALICE2 (manufactured by JEOL Ltd.) was used to perform analysis by the following method. 1 After adjusting the phase of the H-NMR chart so that the baseline is smooth, the average point is set to 20 and the baseline is automatically corrected. Next, the peak 1 of heavy water, which is the measurement solvent, is automatically set to the position of 4.65 ppm as a reference. Figure 1 In this way, the hydrogen peak 6 of the methyl group derived from the boron-containing compound (B) appearing in the range of 1.2 to 1.3 ppm is integrated to find its peak area (area A). Next, the hydrogen peak 5 of the hydrocarbon group derived from the boron-containing compound (B) and the boron-containing compound (C) overlapping in the range of 1.0 to 1.2 ppm is integrated to find its peak area (area B). Furthermore, the hydrogen peak in the range of 1.6 to 2.3 ppm is regarded as the sum of the hydrogen peak 3 of the methylene group derived from PVA and the hydrogen peak 4 of the hydrocarbon group derived from the boron-containing compound (B) and the boron-containing compound (C) overlapping with the hydrogen peak 3 of the methylene group derived from PVA, and the total area of ​​the hydrogen peaks in the range of 1.6 to 2.3 ppm is found (area C). At this time, the area (area A) of the hydrogen peak 6 of the methyl group derived from the boron-containing compound (B) that does not overlap with the hydrogen peak derived from PVA and the hydrogen peak derived from the boron-containing compound (C) is used as the basis for the peak area, and is set to 3 in the same way as the number of hydrogen atoms in the methyl group. Thereafter, the area U of the hydrogen peak 4 of the hydrocarbon group of the boron-containing compound (B) and the boron-containing compound (C) overlapping with the hydrogen peak of the methylene group of PVA is subtracted from the area C to calculate the area D. The values ​​obtained by these methods are substituted into the following formula (1) to calculate the content (mass parts) of the boron element derived from the boron-containing compound (B) relative to 100 mass parts of PVA (A). It should be noted that W in the following formula (1) is the number of boron in an average of 1 molecule of the boron-containing compound (B). In addition, the following formula (1) is a formula used when using unmodified PVA. When using modified PVA as a raw material, the following formula (1) needs to be appropriately deformed.

[0128] Content of boron element derived from boron-containing compound (B) relative to 100 parts by mass of PVA (A) (parts by mass)

[0129] ={(Area A / 3) / (Area D / 2)}×(10.811×W / 44.0526)×100(1)

[0130] Next, substitute the value obtained in the following formula (2) to calculate the boron content of the boron-containing compound (C) in an average of 100 parts by mass of PVA (A). It should be noted that X in the following formula (2) is the number of hydrogen atoms of the hydrocarbon group derived from the boron-containing compound (B) overlapping with the hydrogen peak of the hydrocarbon group derived from the boron-containing compound (C) in the range of 1.0 to 1.2 ppm, and Y is the number of hydrogen atoms in the hydrocarbon group derived from the boron-containing compound (C) per molecule on average in the range of 1.0 ppm to 1.2 ppm. In addition, Z is the number of boron atoms in the boron-containing compound (C) per molecule on average. It should be noted that the following formula (2) is a formula used when unmodified PVA is used, and when modified PVA is used as a raw material, the following formula (2) needs to be appropriately deformed.

[0131] Content of boron element derived from the boron-containing compound (C) relative to 100 parts by mass of PVA (A) (parts by mass) = {(area A / 3) / (area D / 2)}×{(area B)-X} / Y×(10.811×Z / 44.0526)×100(2)

[0132] In formula (2), 10.811 is the atomic weight of boron, and 44.0526 is the molecular weight of the average repeating unit of unmodified PVA. Figure 1 of 1 The H-NMR chart was obtained by measuring the polarizing film of Example 1.

[0133] [Determination of the boron element content derived from the boron-containing compound (B) or the boron-containing compound (C) in a polarizing film containing only one of the boron-containing compound (B) and the boron-containing compound (C)]

[0134] The measurement was performed by referring to the method of Patent Document 6 in the following procedure. A polarizing film or a stretched film was dissolved in heavy water so that the content thereof was 0.003 mass %, and then concentrated by a rotary evaporator so that the content thereof was 0.15 mass %. 1 H-NMR measurement sample. 1 H-NMR (manufactured by JEOL Ltd., JNM-AL400: 400 MHz) measurement was performed at 80°C, and the number of accumulations was set to 256. ALICE2 (manufactured by JEOL Ltd.) was used to perform analysis by the following method. 1After adjusting the phase of the H-NMR graph so that the baseline is smooth, the average point is set to 20, and the baseline is automatically corrected. Next, it is automatically set as a reference in such a way that the peak of heavy water as the measuring solvent reaches the position of 4.65ppm. Thereafter, the hydrogen peak of the hydrocarbon group derived from the boron-containing compound (B) or the boron-containing compound (C) is integrated to find its peak area (area E). At this time, the hydrogen peak area of ​​the hydrocarbon group derived from the boron-containing compound (B) or the boron-containing compound (C) that does not overlap with the hydrogen peak derived from PVA is added (area F), and it is used as the basis of the peak area, and the number of hydrogen atoms of the corresponding hydrocarbon group of the boron-containing compound (B) or the boron-containing compound (C) is set in the same way as the value of area F. Next, the hydrogen peak in the range of 1.6ppm to 2.3ppm is regarded as the sum of the hydrogen peak of the methylene group derived from PVA and the hydrogen peak of the hydrocarbon group contained in the boron-containing compound (B) or the boron-containing compound (C) that overlaps with the hydrogen peak of the methylene group derived from PVA, and the peak area (area G) is found. Thereafter, the area H is calculated by subtracting the number of hydrogen atoms of the hydrocarbon group derived from the boron-containing compound (B) or the boron-containing compound (C) that overlaps with the hydrogen peak of the methylene group derived from PVA from the area G. The values ​​obtained by these methods are substituted into the following formula (3) to calculate the content (parts by mass) of the boron element derived from the boron-containing compound (B) or the boron-containing compound (C) relative to 100 parts by mass of PVA (A). It should be noted that S in the following formula (3) is the number of hydrogen atoms of the hydrocarbon group contained in the boron-containing compound (B) or the boron-containing compound (C) that does not overlap with the peak of PVA, and T is the number of boron atoms in an average of one molecule of the boron-containing compound (B) or the boron-containing compound (C). It should be noted that formula (3) is a formula used when unmodified PVA is used, and when modified PVA is used as a raw material, the following formula (3) needs to be appropriately deformed.

[0135] Content of boron element derived from the boron-containing compound (B) or the boron-containing compound (C) relative to 100 parts by mass of PVA (A) (parts by mass)

[0136] ={(area F / S) / (area H / 2)}×(10.811×T / 44.0526)×100(3)

[0137] In formula (3), 10.811 is the atomic weight of boron, and 44.0526 is the molecular weight per 1 mol of the average repeating unit of the unmodified PVA.

[0138] [Calculation of Total Boron Element Content (Mass %) in Polarizing Film]

[0139] The mass [I(g)] of the polarizing film is measured, and the polarizing film is dissolved in 20 mL of distilled water in such a way that the content of the polarizing film reaches 0.005% by mass. The aqueous solution in which the polarizing film is dissolved is used as a measurement sample, and its mass [J(g)] is measured. Thereafter, the boron concentration [K(ppm)] of the measurement sample is measured using a multi-pass ICP emission spectrometer (ICP) manufactured by Shimadzu Corporation. Thereafter, the value calculated by substituting the value into the following formula (4) is recorded as the total boron content (mass %) in the polarizing film.

[0140] Total boron content in polarizing film (mass %) = [(K × 10 -6 ×J) / I]×100 (4)

[0141] [Optical properties of polarizing films]

[0142] (1) Measurement of single-unit transmittance Ts after visual sensitivity correction

[0143] The visual sensitivity corrected single transmittance Ts of the polarizing film obtained in the following examples or comparative examples (hereinafter, "visual sensitivity corrected single transmittance Ts" may be referred to as "transmittance Ts") is measured using a spectrophotometer with an integrating sphere (manufactured by JASCO Corporation, "V-7100") and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan Taylor polarizer. A sample of 4 cm in the stretching direction and 2 cm in the width direction of the polarizing film is collected from the central part of the obtained polarizing film. For the collected polarizing film, the MD transmittance (%) and TD transmittance (%) in the range of 380nm to 780nm are measured, and the transmittance Ts (%) is calculated using the "Polarizing Film Evaluation Program" (manufactured by JASCO Corporation). Here, "MD transmittance" refers to the transmittance (%) when the direction of the polarized light leaving the Glan Taylor polarizer is set to be parallel to the transmission axis of the polarizing film sample. The “TD transmittance” is the transmittance (%) when the direction of polarized light leaving the Glan Taylor polarizer is perpendicular to the transmission axis of the polarizing film sample. The transmittance Ts is a value calculated from the MD transmittance and the TD transmittance by multiplying the sensitivity correction called visual sensitivity correction.

[0144] (2) Determination of polarization degree V for visual sensitivity correction

[0145] The polarizing film samples used in the measurement of the transmittance Ts (%) were measured using a spectrophotometer with an integrating sphere (manufactured by JASCO Corporation, "V7100") and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan Taylor polarizer. The MD transmittance (%) and TD transmittance (%) of the sample in the range of 380nm to 780nm were measured, and the visual sensitivity corrected polarization degree V (%) was calculated using the "Polarizing Film Evaluation Program" (manufactured by JASCO Corporation) (hereinafter, "visual sensitivity corrected polarization degree V" may be referred to as "polarization degree V").

[0146] [Shrinkage force of polarizing film]

[0147] The shrinkage force is measured using Autograph "AG-X" with a thermostatic chamber and a camera-type tensile tester "TR ViewX120S" manufactured by Shimadzu Corporation. For the measurement, a polarizing film that has been humidified at 20°C / 20% RH for 18 hours is used. After the thermostatic chamber of the Autograph "AG-X" is set to 20°C, a rectangular polarizing film [15 cm in the length direction (stretching direction), 1.5 cm in the width direction] is mounted on a clamp (with a clamp spacing of 5 cm), and the temperature of the thermostatic chamber is raised to 80°C at the same time as the stretching begins. The polarizing film is stretched at a speed of 1 mm / min, and the stretching is stopped when the tension reaches 2N. The tension is measured in this state until 4 hours later. At this time, the distance between the clamps changes due to thermal expansion, so a marking label is attached to the clamp, and the camera-type tensile tester "TR ViewX120S" is used to correct only the amount of movement of the marking label attached to the clamp so that the distance between the clamps becomes constant, and the measurement is performed at the same time. It should be noted that when a minimum value of tension is generated at the beginning of the measurement (within 10 minutes from the start of the measurement), the minimum value of tension is subtracted from the measured value of tension 4 hours later, and the difference is recorded as the shrinkage force of the polarizing film. When no minimum value is generated, the tension at the time of stopping stretching, that is, 2N, is subtracted from the measured value of tension 4 hours later, and the resulting value is recorded as the shrinkage force of the polarizing film.

[0148] [Moisture and heat resistance]

[0149] The moisture and heat resistance of the polarizing film is evaluated using a spectrophotometer with an integrating sphere (manufactured by JASCO Corporation, "V7100") and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan Taylor polarizer. The collected polarizing film is fixed on a metal frame to prepare an evaluation sample. Next, the orthogonal transmittance (%) at 610 nm of the evaluation sample at the initial time (0 hour) is measured using a spectrophotometer with an integrating sphere (manufactured by JASCO Corporation, "V7100") and an automatic polarizing film measuring device VAP-7070S (manufactured by JASCO Corporation) equipped with a Glan Taylor polarizer. It should be noted that the orthogonal transmittance (%) refers to the value calculated by the following formula (5). In addition, by substituting the calculated orthogonal transmittance at 610 nm into the following formula (6), the orthogonal absorbance A at 610 nm at the initial time (0 hour) is calculated. 0 . Subsequently, the orthogonal transmittance (%) at 610 nm was measured after the evaluation sample was left to stand for 1 hour, 2 hours, 4 hours, 6 hours, and 8 hours in an atmosphere of 60°C / 90% RH using a small constant temperature and humidity machine (manufactured by Yamato Scientific Co., Ltd., "IW223"), and the orthogonal absorbance A at each standing time was calculated by substituting the result into the following formula (6). It should be noted that the orthogonal transmittance was measured using the same evaluation sample until 8 hours later. Next, a graph was used to show the relationship between the test time and Ln (A / A 0 ) is approximated as a linear equation passing through the origin, and its slope is calculated. The slope is recorded as the attenuation coefficient of the PVA-iodine complex, which is used as an indicator of fading (an indicator of moisture and heat resistance) in the present invention. The smaller the attenuation coefficient, the faster the fading of the iodine-based polarizing film. Therefore, a small attenuation coefficient indicates low moisture and heat resistance.

[0150] Orthogonal transmittance at 610 nm at each standing time (%) = (MD transmittance at 610 nm at each standing time × TD transmittance at 610 nm at each standing time) / 100 (5) Absorbance A at each standing time

[0151] =2-Log (orthogonal transmittance at 610 nm at each standing time) (6)

[0152] [Swelling degree of PVA film]

[0153] The PVA film was cut into 5 cm × 10 cm and immersed in 1000 mL of distilled water at 30°C for 30 minutes. Thereafter, the PVA film was taken out, the moisture on the surface of the PVA film was wiped with filter paper, and the mass (mass L) of the PVA film after immersion was measured. Thereafter, the PVA film was placed in a dryer at 105°C and dried for 16 hours, and the mass (mass M) of the dried PVA film was measured. The swelling degree of the PVA film was calculated by substituting the values ​​of mass L and mass M into the following formula (7).

[0154] Swelling degree (%) = (mass L / mass M) × 100 (7)

[0155] [Example 1]

[0156] An aqueous solution containing 100 parts by mass of PVA (saponification degree of 99.9 mol%, polymerization degree of 2400), 10 parts by mass of glycerol as a plasticizer and 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, with a PVA content of 9% by mass, is used as a film-making stock solution, and is dried on a metal roller at 80°C. The resulting film is heat-treated in a hot air dryer at 120°C for 10 minutes, thereby producing a PVA film with a thickness of 30 μm that is adjusted so that the swelling degree of the PVA film reaches 200%.

[0157] In the central part of the width direction of the PVA film obtained in this way, a sample of 5 cm in width × 9 cm in length is cut in a manner that can be uniaxially stretched in the range of 5 cm in width × 5 cm in length. The sample is immersed in pure water at 30°C for 30 seconds, and uniaxially stretched to 1.1 times in the length direction, and a swelling treatment is performed. Next, it is immersed in an aqueous solution (dyeing treatment bath) (temperature 30°C) containing 0.043% by mass of iodine and 4.3% by mass of potassium iodide (KI) for 60 seconds, and uniaxially stretched to 2.2 times (2.4 times as a whole) in the length direction to adsorb iodine. Further, it is immersed in an aqueous solution (cross-linking treatment bath) (temperature 30°C) containing 3.0% by mass of boric acid and 3% by mass of potassium iodide for 45 seconds, and uniaxially stretched to 1.2 times (2.7 times as a whole) in the length direction to adsorb boric acid. Furthermore, it was immersed in an aqueous solution (stretching treatment bath) (temperature 60°C) containing 4.0% by mass of boric acid and 6.0% by mass of potassium iodide, and uniaxially stretched to 2.2 times (6.0 times as a whole) in the length direction to orient it. Thereafter, it was immersed in an aqueous solution (first fixing treatment bath) (temperature 30°C) containing 0.7% by mass of n-propylboric acid and 3.5% by mass of potassium iodide for 30 seconds. In the first fixing treatment, the PVA film was not stretched (stretching ratio was 1.0 times). Thereafter, it was further immersed in an aqueous solution (second fixing treatment bath) (temperature 50°C) containing 0.5% by mass of 1,4-butanediboric acid and 8.5% by mass of potassium iodide for 100 seconds. In the second fixing treatment, the PVA film was not stretched (stretching ratio was 1.0 times). Finally, it was dried at 60°C for 4 minutes to manufacture a polarizing film.

[0158] The obtained polarizing film was measured 1As a result of H-NMR analysis, a hydrogen peak 6 derived from the methyl group of n-propylboric acid appeared at 1.2 to 1.3 ppm, which did not overlap with the hydrogen peaks of the hydrocarbon groups derived from PVA and 1,4-butanediboric acid, and therefore the peak area (area A) was set to 3. Next, the peak area (area B) of the hydrogen peak 5 that appeared in the range of 1.0 ppm to 1.2 ppm and overlapped with the hydrogens of the hydrocarbon groups derived from n-propylboric acid and 1,4-butanediboric acid was calculated. Thereafter, since the hydrogen peak 3 of the methylene group of PVA overlapped with the hydrogen peak 4 of the hydrocarbon groups derived from n-propylboric acid and 1,4-butanediboric acid, the hydrogen peaks in the range of 1.6 to 2.3 ppm were regarded as the sum of the hydrogen peak 3 of the methylene group of PVA and the hydrogen peak 4 of the hydrocarbon groups derived from n-propylboric acid and 1,4-butanediboric acid, and the total area (area C) of the hydrogen peaks in the range of 1.6 to 2.3 ppm was calculated. Area D is obtained by subtracting the area of ​​the hydrogen peak derived from the hydrocarbon groups of n-propylboric acid and 1,4-butanediboric acid (area U, which corresponds to area B in Example 1) from area C. Substituting these values ​​into the above formula (1) results in a content of 0.49 parts by mass of the boron element derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A). Further, substituting these values ​​into the above formula (2) results in a content of 0.08 parts by mass of the boron element derived from the boron-containing compound (C) relative to 100 parts by mass of PVA (A). The total boron element content in the polarizing film was measured to be 1.9% by mass.

[0159] The optical properties of the obtained polarizing film were measured, and the transmittance Ts was 44.09%, and the polarization degree V was 99.92%. In addition, the shrinkage force of the obtained polarizing film was measured, and the result was 2.7N. In addition, the attenuation coefficient of the PVA-iodine complex was -0.35. These results are shown in Tables 1 and Figure 2 .

[0160] After the first fixing treatment, the PVA film was dried at 60° C. for 4 minutes, and the boron content of the obtained stretched film was measured to be 0.81 parts by mass.

[0161] [Example 2]

[0162] A polarizing film was prepared in the same manner as in Example 1 except that an aqueous solution (temperature 30° C.) containing 0.5% by mass of 1,4-butanediboric acid and 5.5% by mass of potassium iodide was used in the second fixing treatment bath. The measurements and evaluations were performed by the above methods. The results are shown in Tables 1 and Figure 2 .

[0163] [Comparative Example 1]

[0164] A polarizing film was produced in the same manner as in Example 1 except that the second fixing treatment was not performed, and each measurement and evaluation were performed by the above-mentioned methods. The results are shown in Tables 1 and Figure 2 .

[0165] [Comparative Example 2]

[0166] The polarizing film was prepared in the same manner as in Example 1 except that the immersion time in the first fixing treatment bath was set to 100 seconds and the second fixing treatment was not performed, and each measurement and evaluation were performed by the above-mentioned methods. The results are shown in Tables 1 and Figure 2 .

[0167] [Comparative Example 3]

[0168] In the first fixing treatment bath, an aqueous solution (temperature 10°C) containing 1.0% by mass of n-butylboric acid was used. The immersion time in the first fixing treatment bath was set to 20 seconds. No second fixing treatment was performed. Except for this, a polarizing film was prepared in the same manner as in Example 1, and each measurement and evaluation was performed by the above method. At this time, for the measurement of the content of boron element derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A), the boron-containing compound (B) could not be detected when the cumulative number of times was 256. Therefore, the cumulative number of times was changed to 4096, and the content of boron element derived from the boron-containing compound (B) relative to 100 parts by mass of PVA (A) was measured. The results are shown in Tables 1 and Figure 2 .

[0169] [Comparative Example 4]

[0170] The polarizing film was prepared in the same manner as in Example 2 except that the immersion time in the first fixing treatment bath was set to 100 seconds, and each measurement and evaluation were performed by the above-mentioned method. The results are shown in Table 1. However, since the boron-containing compound (C) was not adsorbed on the polarizing film, the evaluation of shrinkage force, optical properties and moisture-heat resistance was not performed.

[0171] [Comparative Example 5]

[0172] The first fixing treatment bath used an aqueous solution (temperature 30°C) containing 0.5% by mass of 1,4-butanediboric acid and 4.0% by mass of potassium iodide, and the immersion time in the first fixing treatment bath was set to 100 seconds. The second fixing treatment was not performed. In the same manner as in Example 1, a polarizing film was produced and each measurement and evaluation were performed by the above-mentioned method. The results are shown in Tables 1 and Figure 2 .

[0173] [Comparative Example 6]

[0174] A polarizing film was prepared in the same manner as in Example 1 except that an aqueous solution (temperature 50° C.) containing 1.0% by mass of 1,4-butanediboric acid and 5.5% by mass of potassium iodide was used in the second fixing treatment bath. The measurements and evaluations were performed by the above methods. The results are shown in Tables 1 and Figure 2 .

[0175] [Comparative Example 7]

[0176] The first fixing treatment bath used an aqueous solution (fixing treatment bath) (temperature 50° C.) containing 0.2% by mass of n-propylboric acid, 0.3% by mass of 1,4-butanediboric acid, and 5.0% by mass of potassium iodide. The immersion time in the first fixing treatment bath was set to 100 seconds. The second fixing treatment was not performed. In the same manner as in Example 1, a polarizing film was prepared and each measurement and evaluation were performed by the above-mentioned method. The results are shown in Tables 1 and Figure 2 .

[0177] [Comparative Example 8]

[0178] A polarizing film was prepared in the same manner as in Example 1 except that an aqueous solution (temperature 30° C.) containing 2.0% by mass of boric acid and 2.0% by mass of potassium iodide was used in the first fixing treatment bath, and the immersion time in the first fixing treatment bath was set to 100 seconds and the second fixing treatment was not performed. Each measurement and each evaluation were performed by the above-mentioned method. The results are shown in Tables 1 and 2. Figure 2 .

[0179] [Comparative Example 9]

[0180] The first fixing treatment bath used an aqueous solution (temperature 30° C.) containing 0.5% by mass of boric acid and 2.0% by mass of potassium iodide, and the immersion time in the first fixing treatment bath was set to 100 seconds. The second fixing treatment was not performed. In the same manner as in Example 1, a polarizing film was produced and each measurement and evaluation were performed by the above-mentioned method. The results are shown in Tables 1 and Figure 2 .

[0181] [Comparative Example 10]

[0182] A polarizing film was produced in the same manner as in Example 1 except that the first fixing treatment and the second fixing treatment were not performed, and each measurement and each evaluation were performed by the above-mentioned methods. The results are shown in Tables 1 and Figure 2 .

[0183] [Comparative Example 11]

[0184] As the first fixing treatment bath, an aqueous solution containing potassium iodide at a ratio of 2.0 mass % (temperature 30° C.) was used, and the immersion time in the first fixing treatment bath was set to 5 seconds. Except that the second fixing treatment was not performed, a polarizing film was produced in the same manner as in Example 1, and each measurement and each evaluation were performed by the above-mentioned method. The results are shown in Tables 1 and Figure 2 .

[0185] [Comparative Example 12]

[0186] A polarizing film was produced in the same manner as in Comparative Example 11 except that the immersion time in the first fixing treatment bath was set to 20 seconds, and each measurement and evaluation were performed by the above-mentioned methods. The results are shown in Tables 1 and Figure 2 .

[0187] In Example 2 and Comparative Examples 1 to 12, an aqueous solution (temperature 30° C.) containing iodine and potassium iodide at a mass ratio of 1:100 was used in the dyeing treatment bath. At this time, the concentrations of iodine and potassium iodide in the dyeing treatment bath were adjusted so that the transmittance of the polarizing film after drying was 43.8% to 44.2%.

[0188]

[0189] Figure 2 This is a graph obtained by plotting the shrinkage force on the horizontal axis and the attenuation coefficient of the PVA-iodine complex on the vertical axis for the polarizing films of Examples 1 and 2 and Comparative Examples 1 to 12. Figure 2 As shown, the shrinkage force of the polarizing films of Examples 1 and 2 satisfying the requirements of the present invention is less than 5N, and the attenuation coefficient of the PVA-iodine complex is not less than -0.5, which shows that the shrinkage force is low and the moisture and heat resistance is excellent.

[0190] On the other hand, the polarizing films of Comparative Examples 1 to 3, in which only the former of the boron-containing compound (B) and the boron-containing compound (C) are adsorbed, have insufficient reduction in either of the shrinkage force or the moisture and heat resistance. The polarizing film of Comparative Example 5, in which only the latter of the boron-containing compound (B) and the boron-containing compound (C) are adsorbed, and the polarizing film of Comparative Example 6, in which the concentration of the boron-containing compound (C) during the second fixing treatment is high and the boron-containing compound (C) is excessively adsorbed, have sufficient moisture and heat resistance, but insufficient reduction in shrinkage force. The polarizing film of Comparative Example 7, in which an aqueous solution containing a boron-containing compound (B) and a boron-containing compound (C) is used and both are adsorbed simultaneously, has a low mass ratio (B / C) and insufficient reduction in shrinkage force. Furthermore, the polarizing films of Comparative Examples 10 to 12, in which neither the boron-containing compound (B) nor the boron-containing compound (C) are contained, have insufficient reduction in either of the shrinkage force or the moisture and heat resistance or both.

[0191] Description of Reference Numerals

[0192] 1 Hydrogen peak from heavy water used as the measurement solvent

[0193] 2 Hydrogen peak from the methine group of PVA

[0194] 3 Hydrogen peaks from the methylene groups of PVA

[0195] 4 Hydrogen peaks originating from hydrocarbon groups contained in the boron-containing compound (B) and the boron-containing compound (C) overlapping with the hydrogen peak originating from PVA

[0196] 5 Hydrogen peak derived from hydrocarbon groups that does not overlap with the hydrogen peak derived from PVA but overlaps with the hydrogen peak derived from boron-containing compound (B) and boron-containing compound (C) 6 Hydrogen peak derived from methyl group of boron-containing compound (B) that does not overlap with the hydrogen peak derived from PVA and the hydrogen peak derived from boron-containing compound (C)

Claims

1. A polarizing film comprising: polyvinyl alcohol (A), at least one boron-containing compound (B) selected from a monoorganic boronic acid represented by the following formula (I) and a compound capable of being converted into the monoorganic boronic acid in the presence of water, and at least one boron-containing compound (C) selected from a diorganic boronic acid represented by the following formula (II) and a compound capable of being converted into the diorganic boronic acid in the presence of water, The mass ratio B / C of the boron element derived from the boron-containing compound (B) to the boron element derived from the boron-containing compound (C) is 4.0 to 8.0, and the content of the boron element derived from the boron-containing compound (C) is 0.05 to 0.09 parts by mass based on 100 parts by mass of the polyvinyl alcohol (A). [Chemistry 1] In formula (I), R 1 is a monovalent aliphatic group having 1 to 20 carbon atoms, R 1 Connected to the organic boronic acid group via a boron-carbon bond; [Chemistry 2] In formula (II), R 2 is a divalent aliphatic group having 1 to 20 carbon atoms, R 2 It is connected to the organic boronic acid group through a boron-carbon bond.

2. The polarizing film according to claim 1, wherein R 1 and R 2 It is a saturated aliphatic group.

3. The polarizing film according to claim 1 or 2, wherein: R 1 and R 2 It is an aliphatic hydrocarbon group.

4. The polarizing film according to claim 1 or 2, wherein R 1 The number of carbon atoms is 2 to 5, R 2 The number of carbon atoms is 3 to 5.

5. The method for producing a polarizing film according to any one of claims 1 to 4, characterized in that: In a method for manufacturing a polarizing film comprising a dyeing treatment of a polyvinyl alcohol film with a dichroic dye and a stretching treatment of the film by uniaxially stretching, the film comprises: a treatment of immersing the film in an aqueous solution containing a boron-containing compound (B) and a treatment of immersing the film in an aqueous solution containing a boron-containing compound (C).

6. The method for manufacturing a polarizing film according to claim 5, wherein: After the polyvinyl alcohol film is immersed in an aqueous solution containing the boron-containing compound (B), the film is immersed in an aqueous solution containing the boron-containing compound (C).

7. The method for manufacturing a polarizing film according to claim 6, wherein: The content of the boron element derived from the boron-containing compound (B) in the polyvinyl alcohol film immersed in the aqueous solution containing the boron-containing compound (B) is 0.1 to 1.3 parts by mass based on 100 parts by mass of the polyvinyl alcohol (A).

Citation Information

Patent Citations

  • Polarizing film having superior durability and its production

    JP1989084203A

  • Polarizing film and its production

    JP1994235815A

  • Production of polarizing film

    JP1994265727A

  • Polarizing film and manufacturing method thereof and polarizer

    JP2013148806A

  • Manufacturing method of polarizer

    JP2018180022A